2018
DOI: 10.1002/app.47155
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in mechanical and hygroscopic properties of modified SA fiber crosslinking with PEGDE

Abstract: Modified sodium alginate (mSA) fiber is prepared through the wet spinning process using poly(ethylene glycol) diglycidyl ether (PEGDE, the molecular weight of PEGDE is 400) as the crosslinking agent to improve the mechanical and hygroscopic properties. Flowing property of the spinning solution and properties of the mSA fiber are characterized by DV-C digital viscometer, single fiber electronic tensile strength tester and other instruments. Results show that viscosity of the spinning solution dropped firstly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Excess amount of PCL-N polymers (CP-0.5) reduced the degree of cross-linking again, resulting a damaged pore structure and cracked skeletal surface, as shown in Figure c. Similar phenomenon that the degree of cross-linking decreases with the excess concentration of cross-linking agent can be found in many previous literature reports. The possible mechanism is shown in Figure . PCL-N takes precedence to grafting onto the surface of CNC-C at one of its terminals due to the stronger mobility of the free PCL-N molecular chains compared with that of the grafted molecular chains.…”
Section: Resultssupporting
confidence: 73%
“…Excess amount of PCL-N polymers (CP-0.5) reduced the degree of cross-linking again, resulting a damaged pore structure and cracked skeletal surface, as shown in Figure c. Similar phenomenon that the degree of cross-linking decreases with the excess concentration of cross-linking agent can be found in many previous literature reports. The possible mechanism is shown in Figure . PCL-N takes precedence to grafting onto the surface of CNC-C at one of its terminals due to the stronger mobility of the free PCL-N molecular chains compared with that of the grafted molecular chains.…”
Section: Resultssupporting
confidence: 73%
“…As discussed previously, the physicochemical properties of alginate can depend upon the G:M; where higher concentrations of G are more stable when compared to high M content (Axpe and Oyen, 2016). The molecular weight of the crosslinking agent and exposure time can be altered in order to regulate the elasticity (Young's) modulus of a hydrogel; for instance, using increasing concentrations of poly(ethyleneglycol)diamine as a crosslinker has been shown to increase the viscosity and toughness of the hydrogel (Naghieh et al, 2018;Meng et al, 2019). Another study showed an increase in elasticity modulus with increasing concentrations of Ca 2+ which enabled an alginate-based hydrogel to improve mechanical properties whilst maintaining high ionic strength (Matyash et al, 2014).…”
Section: Plant-derived Biomaterials Alginatementioning
confidence: 99%
“…Poly(ethylene glycol)diglycidyl ether (PEGDE) is a derivative of poly(ethylene glycol) (PEG), which has been widely used for crosslinking of potential materials for biomedical applications. [46][47][48][49] The research of Solazzo et al 50 introduced PEGDE to crosslink PEDOT:PSS for bio-applications. On a molecular level, the crosslinking occurs via the PEGDE epoxy ring interacting with the sulfonic groups of the PSS.…”
Section: Pedot In Biologymentioning
confidence: 99%